Sustainable tourism marketing strategy using the EFINEEL model in coastal communities - Cempena, Ida Bagus; Ratnawati, Tri; Sitohang, Arga Christian (LPPM ISNJ Bengkalis, 2025)
Purpose – Sustainable tourism holds significant potential for enhancing the economic welfare of coastal communities; however, marketing strategies in Minapolitan areas, such as Gosari village Gresik, remain suboptimal, particularly in integrating social and environmental aspects. This study examines the effectiveness of the EFINEEL bottom line model, encompassing seven key dimensions: economy, fishermen, social inclusion, nature, community empowerment, ecology, and local involvement. Method – This study uses a quantitative approach with partial least squares-structural equation modeling (PLS-SEM) and 106 purposively selected respondents. Findings – The findings show that local involvement strongly influences social inclusion, while community empowerment drives economic welfare, with ecological sustainability also positively impacting the outcomes. The EFINEEL model proves effective in formulating practical, sustainable tourism strategies that integrate economic, social, and environmental dimensions. Implications – Theoretically, this study advances sustainable tourism theory by combining the triple bottom-line framework with grassroots-based governance. It demonstrates that community-driven approaches, placing local agencies at the center, lead to more effective sustainable theoretical outcomes, emphasizing the importance of participatory models for destination development in underrepresented rural and coastal areas. This research challenges traditional top-down models and advocates for inclusive, locally rooted governance to achieve long-term sustainability.